PAYMENT INFORMATION SYSTEM ADMINISTRATION COURSE IN LPK INFORMATION - Ade Nasori; Dra. Ida Ayu Wiyastiti. M. KOM (Jurnal Sistem Informasi, 1996)
Because the old system is still done manually it will require a long time. whereas with this new system, where the process is done by computerized hence requires only a relatively short time. As a business entity which is engaged in computer education, with the existence of this computerized system will provide insight to students or prospective students about the importance of the role of computers in the field to support a business.